Real-time monitoring of Solar Battery Charging Station - Priyanka, Mirza Karishma; Chowdhury, Abrar Alvi; Mahmud, Bushra; Chowdhury, Sheri Jahan; Azad, Akm M.M.Abdul Malek (© 2016 IEEE, 2018)
This conference paper was published in the International Conference on Computation of Power, Energy Information and Communication, ICCPEIC 2016; Melmaruvathur, Chennai; India; 20 April 2016 through 21 April 2016 [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/ICCPEIC.2016.7557249 The Journal's website is at: https://ieeexplore.ieee.org/document/7557249/